Peran Dakwah Aplikasi Durioo+ Terhadap Pengamalan Agama Anak Di Kolej Universiti Islam Zulkifli Muhammad Malaysia - Binti Mohammed Zuhilmi, Siti Nabila; Razzaq, Abdur; Randicha Hamandia, Muhammad (Liwaul Dakwah: Jurnal Kajian Dakwah dan Masyarakat Islam, 2025)
This study aims to analyze the Role of Durioo+ Application Da'wah on Children's Religious Practice at the Islamic University of Zulkifli Muhammad College, Malaysia. The sample of this study was the children of lecturers from KUIZM aged 12 years and under. The development of media and digitalization today has had many impacts on children. Various free animation platforms have emerged and offer a variety of content that can be accessed freely. In this fast-paced digital atmosphere, without strict supervision, children can easily access content that is not appropriate for their age. Imagine, in the midst of the pleasure of watching animation that should be educational, they are actually presented with themes that violate sharia. This clearly damages children's views and thoughts about their religious identity. This study uses a descriptive qualitative method, using 3 data collection instruments, namely interviews, observations and documentation. Based on the results of the study, it can be concluded that this application makes a significant contribution to introducing and strengthening the understanding of Islamic values ​​to children. The content focus on worship, stories of the prophets, daily prayers, and Islamic manners has proven effective in forming positive religious habits that are relevant to everyday life.